Dependence of the Efficiency of the Nonlinear‐Optical Response of Materials on their Linear Permittivity and Permeability. Issue 12 (8th November 2021) - Solís, Diego M.; Boyd, Robert W.; Engheta, Nader
Abstract: The dependence of the efficiency of various nonlinear‐optical processes on the background linear relative electric permittivity ϵ and magnetic permeability μ of the material is analytically and numerically investigated. The conversion efficiency of low‐order harmonic‐generation processes, as well as the increase rate of Kerr‐effect nonlinear phase shift and nonlinear losses from two‐photon absorption (TPA), are seen to increase with decreasing ϵ and/or increasing μ. The rationale and physical insights behind this nonlinear response are also discussed, particularly its enhancement in ϵ‐near‐zero (ENZ) media. This behavior is consistent with the experimental observation of intriguingly high effective nonlinear refractive indices in degenerate semiconductors such as indium tin oxide and aluminum oxide (where the nonlinearity is attributed to a modification of the energy distribution of conduction‐band electrons due to laser‐induced electron heating) at frequencies with vanishing real part of the linear permittivity. Such strong nonlinear response can pave the way for a new paradigm in nonlinear optics with much higher conversion efficiencies and therefore better miniaturization capabilities and power requirements for next‐generation integrated nanophotonics. It is concluded that the major contribution to the enhanced nonlinear response of ENZ materials arises from propagation effects, that is, the appearance of ϵ and μ in the reduced wave equation describing the interaction. Abstract : A theoretical study is presented on the dependence of the efficiency of several nonlinear‐optical processes upon a material's linear electric permittivity and magnetic permeability: the conversion efficiency of harmonic generation, the Kerr‐induced nonlinear phase shift, and nonlinear losses from two‐photon absorption are shown to increase with decreasing permittivity and/or increasing permeability.